Integrated photonic devices for realising photonic quantum computing: part 1 - Lee, Wen Wei (Nanyang Technological University, 2023)
Transition Metal Dichalcogenides (TMDs) have emerged as a promising class of materials for developing Photonic Integrated Circuits (PICs) and practical quantum processors, mainly due to their unique advantages, such as convenient on-chip integration. In this work, we study the effects of strain on the emission wavelength and carrier lifetime in 2D materials, focusing on WSe2 and its strong light-matter interaction, tunable emission, and high electron mobility. We demonstrate the red-shifting of the emission wavelength and reduced carrier lifetime by adding stressor layers. We show that the geometry of stressors can adjust the amount of wavelength shift, suggesting the possibility of developing wavelength-tunable light sources.